Akuntabilitas Keuangan Desa: Perspektif Masyarakat pada Pemerintah Nagari Panyakalan Kecamatan Kubung Kabupaten Solok - Mulya, Ardyzal; Deviani, Deviani (Universitas Negeri Padang, 2024)
This research aims to determine village financial accountability from the perspective of village communities. This research is qualitative research with phenomenological approach. Data collection involved in-depth interview and documentations. The result of this study shows that village financial accountability from the perspective of village communities in Panyakalan Village is still categorized as low. The availability of information is still not optimal, the intensity of discussions is still low, and the consequences of sanctions are still not optimal.